Carotenoid profiling from 27 types of paprika (Capsicum annuum L.) with different colors, shapes, and cultivation methods. (15th June 2016) - Kim, Ji-Sun; An, Chul Geon; Park, Jong-Suk; Lim, Yong Pyo; Kim, Suna
Highlights: Twelve carotenoids were simultaneously identified and quantified by UPLC. We analyzed six carotenoids in red paprika and nine in orange and yellow paprika. Orange paprika is a great source of zeaxanthin regardless of shapes and cultivation methods. We found new red cultivar containing high level of zeaxanthin. Abstract: In this study, we investigated carotenoid profiles and contents from 27 types of paprika with different colors (red, orange, and yellow), shapes (blocky and conical), and cultivation methods (soil and soilless). We simultaneously analyzed 12 kinds of carotenoids using UPLC equipped with an HSS T3 column for 30 min, and we identified six kinds of carotenoids in red paprika and nine types in orange and yellow paprika. Zeaxanthin concentrations in orange paprika were in the range of 85.06 ± 23.37–151.39 ± 5.94 mg/100 g dry weight (dw), which shows that orange paprika is a great source of zeaxanthin. Generally, red paprika is a great source of capsanthin. However, a new cultivar, 'Mini Goggal Red', contained large amounts of zeaxanthin (121.41 ± 30.10 mg/100 g dw) even though its visible color is red. This is very meaningful considering that consumers have a preference for red color and the potent functional value of zeaxanthin. Carotenoid profiles and concentrations in blocky and conical type paprika were not significantly different in red paprika except the 'Mini Goggal Red' cultivar and yellow paprika. Blocky type orange paprika contains plenty of zeaxanthin, unlike conical type orange paprika. Three new cultivars of the conical type were cultivated in both soil culture and soilless culture in the same province, and carotenoid profiles and concentrations were similar, showing that both cultivations methods can be used.